Subsurface structural mapping of Northern Nasser Lake region, Aswan, Egypt, using Bouguer data - SALEH, Salah (Contributions to Geophysics and Geodesy, 2011)
In this study, we attempt to delineate the subsurface structures for thetectonic active region of Northern Nasser Lake using integrated interpretation techniquesof gravity data with seismicity. The depths to the gravity sources, and the locations of thecontacts of density contrast were estimated. Two methods were used for estimating sourcedepths and contact locations: horizontal gradient (HG) and Euler deconvolution methods.Moreover, power spectral analysis, bandpass and upward continuation techniques wereapplied to evaluate the shallow and deep seated structures. Shallow depth structureswere ranging between 0.30 km and 0.80 km. However, two average levels (interfaces) atdepth 3.1 km and 7.2 km below the measuring level were revealed for the intermediateand deep seated structures respectively. Results of Euler deconvolution method suggestedthat, in the eastern part of the area, the basement could be observed on the ground and hasbecome deeper in the central part. The interpreted structural map reveals that the area isaffected by a set of faults trending mainly in the NW, E–W, N–S and NE–SW directions.Actually, this map has confirmed the idea that the intersections between the N–S and E–W striking faults along Nasser Lake area have generated seismic pulses. Moreover, threeseismic zones (Z1, Z2 and Z3) are well correlated with the fault trends of the subsurfacestructures as derived from the horizontal gradient map. The present results suggest thatthere exist seismically-active fault east of High Dam, passing throughout Aswan reservoirfrom north to south. This fault is occupying region of high stress values which maygenerate large earthquakes in future, as it has long extension over several kilometers.Furthermore, the evaluated intruded volcanic bodies are found almost at the intersectionsbetween the E–W and NW oriented faults.